2020
DOI: 10.21608/jppp.2020.111730
|View full text |Cite
|
Sign up to set email alerts
|

Insects' Deterrent Flavonoids from Cynara cardunculus for Controlling Cotton Leafworm; Spodoptera littoralis. الفلافونیدات الرادعة للحشرات من نبات الخرشوف البری , سینارا کارینکولارس لمکافحة دودة ورق القطن.

Abstract: Globally, striving to find eco-friendly pest control agents increased day after day toward plant metabolites. Through current work, three flavonoids were isolated from Cynara cardunculus and identified as Apigenin, Luteolin, and Luteolin-7-O-glucoside using UV, IR, and MS spectrometry analyses. The three compounds were evaluated for their anti-feeding and deterrence activity against 4th instar larvae of cotton leafworm Spodoptera littoralis using both dual and no-choice leaf disk tests. results revealed that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…One explanation for this is the increased level of flavonoids, such as apigenin and luteolin derivatives, that are constitutively found in Mp fad5 mutants. These flavonoids have been shown to have antifeedant activity (Golawska & Lukasik, 2012; El Shafeiy & Abdelaziz, 2020) and thus may have contributed to the protection of the mutant plants. Furthermore, it has been found that ω3 VLPUFA (Very Long Chain PUFA) favours larvae development (Twining et al ., 2016), and therefore, the reduced levels in Mp fad5 may also contribute to the mutant plants’ success against herbivorous insects.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this is the increased level of flavonoids, such as apigenin and luteolin derivatives, that are constitutively found in Mp fad5 mutants. These flavonoids have been shown to have antifeedant activity (Golawska & Lukasik, 2012; El Shafeiy & Abdelaziz, 2020) and thus may have contributed to the protection of the mutant plants. Furthermore, it has been found that ω3 VLPUFA (Very Long Chain PUFA) favours larvae development (Twining et al ., 2016), and therefore, the reduced levels in Mp fad5 may also contribute to the mutant plants’ success against herbivorous insects.…”
Section: Discussionmentioning
confidence: 99%